2019
DOI: 10.1002/ep.13298
|View full text |Cite
|
Sign up to set email alerts
|

Review of the principal mechanisms, prospects, and challenges of bioelectrochemical systems

Abstract: Bioelectrochemical systems (BES) are commonly utilized to generate green electricity, chemicals, and materials through bioelectrocatalytic processes. Over the years, the growing interests in low carbon energy, wastes valorization and the sustainable bioremediation of environmental pollutants have generated interests in BES such as microbial fuel cells (MFC) and bioelectrochemical fuel cells (BFC). The MFCs are the most advanced BES that can ensure the microbial conversion of chemical energy into electrical ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 86 publications
0
19
0
Order By: Relevance
“…Bioelectrochemical systems (BESs) are becoming some of the most promising technologies to produce renewable energy from waste [26]. Over the past decades, BESs have gained substantial interest due to their inherent sustainability and renewable characteristic [24]. BESs are devices that use electrochemically active microorganisms to catalyze electrochemical reactions to produce bioenergy in various types by using organic matter inside wastes [27].…”
Section: Bioenergy Generation Through Bioelectrochemical Systems In Gcc Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioelectrochemical systems (BESs) are becoming some of the most promising technologies to produce renewable energy from waste [26]. Over the past decades, BESs have gained substantial interest due to their inherent sustainability and renewable characteristic [24]. BESs are devices that use electrochemically active microorganisms to catalyze electrochemical reactions to produce bioenergy in various types by using organic matter inside wastes [27].…”
Section: Bioenergy Generation Through Bioelectrochemical Systems In Gcc Regionsmentioning
confidence: 99%
“…are considered to be the possible solutions for catering to human needs in this region. Recently, bioenergy in bioelectrochemical systems (BESs) has gained extensive interest due to its crucial sustainable and renewable characteristics [24]. Preliminary research in the area of bioenergy has been initiated in the Gulf region [25].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been an ever-increasing interest in biocatalyzed reduction at the cathode (i.e., microbial electrolysis cells, MECs) of many pollutants, including TCE or Cr(VI) ( Palma et al, 2018 ). These systems require an electrode acting as an electron donor (cathode), an electron sink (anode), and microorganisms driving reactions to exploit energy from toxic contaminants ( Modin and Aulenta, 2017 ; Ivase et al, 2020 ). Several studies have demonstrated that MECs, under controlled potentials, may rapidly enhance RD by establishing dechlorinating consortia growing on the biocathode ( Aulenta et al, 2007 , 2011 ; Verdini et al, 2015 ; Zeppilli et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different BESs have been proposed, such as microbial electrolysis cell (MEC), microbial fuel cell (MFC), microbial desalination cell (MDC), enzymatic biofuel cell (EBC), microbial reverse‐electrodialysis cell (MRC), microbial solar cell (MSC), and microbial electrosynthesis cells [50] . Among them the MFCs are the most investigated.…”
Section: Bioelectrochemical Systemsmentioning
confidence: 99%